MicroRNA expression patterns and target prediction in multiple myeloma development and malignancy - Bong, I.P.N.; Ng, C.C.; Baharuddin, P.; Zakaria, Z. (Springer Verlag (Germany), 2017)
Epigenetic changes have emerged as key causes in the development and progression of multiple myeloma (MM). In this study, global microRNA (miRNA) expression profiling were performed for 27 MM (19 specimens and 8 cell lines) and 3 normal controls by microarray. miRNA-targets were identified by integrating the miRNA expression profiles with mRNA expression profiles of the matched samples (unpublished data). Two miRNAs were selected for verification by RT-qPCR (miR-150-5p and miR-4430). A total of 1791 and 8 miRNAs were over-expressed and under-expressed, respectively in MM compared to the controls (fold change ≥2.0; p < 0.05). The miRNA-mRNA integrative analysis revealed inverse correlation between 5 putative target genes (RAD54L, CCNA2, CYSLTR2, RASGRF2 and HKDC1) and 15 miRNAs (p < 0.05). Most of the differentially expressed miRNAs are involved in survival, proliferation, migration, invasion and drug resistance in MM. Some have never been described in association with MM (miR-33a, miR-9 and miR-211). Interestingly, our results revealed 2 miRNAs, which are closely related to B cell differentiation (miR-150 and miR-125b). For the first time, we suggest that miR-150 might be potential negative regulator for two critical cell cycle control genes, RAD54L and CCNA2, whereas miR-125b potentially target RAS and CysLT signaling proteins, namely RASGRF2 and CYSLTR2, respectively. This study has enhanced our understanding on the pathobiology of MM and opens up new avenues for future research in myelomagenesis.